2021
DOI: 10.1097/wnr.0000000000001655
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation affects inflammatory response and anti-apoptosis reactions via regulating miR-210 in epilepsy rat model

Abstract: Background Studies have shown that vagus nerve stimulation (VNS) significantly reduces the frequency of seizures. MicroRNAs (miRNAs) in cerebrospinal fluid are expected to become a new biomarker of epilepsy. Therefore, studying the interaction mechanism between the VNS and miRNAs is hopeful of bringing a new therapeutic direction for the treatment of epilepsy.Methods Kainic acid was used to induce the Sprague-Dawley rat epilepsy model, and the rats were treated with VNS. The miR-210 expression was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…The clinical scores were further supported by the histological results that demonstrated decreased neuronal injury loss and apoptosis in the hippocampus CA1 and cortex region and also maintaining functional state of neurons for the tVNS treated group. This result is also consistent with previous results that suggested that VNS reduced the cell death at 24 h post-ROSC due to increased cerebral blood flow (Kim et al, 2019 ), while VNS mediated anti-inflammatory and and anti-apoptotic effect has also been demonstrated in epilepsy (Bie et al, 2021 ). We further observed an interesting event that out of eight rats which received tVNS, five showed an awakening condition between 25 and 30 min post-ROSC and there were three rats receiving tVNS were able to eat on their own suggesting therapeutic approach of tVNS.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical scores were further supported by the histological results that demonstrated decreased neuronal injury loss and apoptosis in the hippocampus CA1 and cortex region and also maintaining functional state of neurons for the tVNS treated group. This result is also consistent with previous results that suggested that VNS reduced the cell death at 24 h post-ROSC due to increased cerebral blood flow (Kim et al, 2019 ), while VNS mediated anti-inflammatory and and anti-apoptotic effect has also been demonstrated in epilepsy (Bie et al, 2021 ). We further observed an interesting event that out of eight rats which received tVNS, five showed an awakening condition between 25 and 30 min post-ROSC and there were three rats receiving tVNS were able to eat on their own suggesting therapeutic approach of tVNS.…”
Section: Discussionsupporting
confidence: 93%
“…The degree of hippocampal apoptosis was also augmented, suggesting that the downregulation of miR-210 can promote apoptosis of hippocampal neurons. Our findings are consistent with the anti-apoptotic effect of miR-210 under hypoxic conditions described by several authors, but contradict the results of other studies 11 , 25 which requires further research.…”
Section: Discussionsupporting
confidence: 76%
“…Stimulation of both vagal efferents and afferents has shown anti-inflammatory effects, attributed to cholinergic signaling ( 174 ). Experimental data supports positive effect of VNS on neuroinflammation in various animal disease models ( 175 178 ). Importantly, chronic VNS decreased levels of pro-inflammatory cytokines in hippocampus of rats with spontaneous recurrent seizures ( 178 ).…”
Section: Future Perspectivessupporting
confidence: 53%